Nerve Decompression and Restless Legs Syndrome: A Retrospective Analysis - Anderson, James C.; Fritz, Megan L.; Benson, John-Michael; Tracy, Brian L. (Frontiers in Neurology, 2017)
Restless Legs Syndrome (RLS) is a prevalent sleep disorder affecting quality of life, and is often comorbid with other neurological diseases, including peripheral neuropathy. The mechanisms related to RLS symptoms remain unclear, and treatment options are often aimed at symptom relief rather than etiology. RLS may present in distinct phenotypes often described as “primary” vs. “secondary” RLS. Secondary RLS is often associated with peripheral neuropathy. Nerve decompression surgery of the common and superficial fibular nerves is used to treat peripheral neuropathy. Anecdotally, surgeons sometimes report improved RLS symptoms following nerve decompression for peripheral neuropathy. The purpose of this retrospective analysis was to quantify the change in symptoms commonly associated with RLS using visual analog scales (VAS). Methods: Forty-two patients completed VAS scales (0-10) for pain, burning, numbness, tingling, weakness, balance, tightness, aching, pulling, cramping, twitchy/jumpy, uneasy, creepy/crawly, and throbbing, both before and 15 weeks after surgical decompression. Results: Subjects reported significant improvement among all VAS categories except for “pulling” (P = 0.14). The change in VAS following surgery was negatively correlated with the pre-surgery VAS for both the summed VAS (r = -0.58, P < 0.001) and the individual VAS scores (all P < 0.01), such that patients who reported the worst symptoms before surgery exhibited relatively greater reductions in symptoms after surgery. Conclusion: This is the first study to suggest improvement in RLS symptoms following surgical decompression of the common and superficial fibular nerves. Further investigation is needed to quantify improvement using RLS-specific metrics and sleep quality assessments.